A projection-fixed point method for a class of bilevel variational inequalities with split fixed point constraints. (2nd June 2016) - Anh, Tran Viet; Muu, Le Dung
Abstract : We propose a method for solving bilevel split variational inequalities involving strongly monotone operators in the leader problems and nonexpansive mappings in the follower ones. The proposed method is a combination between the projection method for variational inequality and the Krasnoselskii–Mann scheme for fixed points of nonexpansive mappings. Strong convergence of the iterative process is proved. Special cases are considered.